2023
DOI: 10.1021/acsphotonics.2c01866
|View full text |Cite
|
Sign up to set email alerts
|

Automated Discovery and Optimization of 3D Topological Photonic Crystals

Abstract: Topological photonic crystals have received considerable attention for their ability to manipulate and guide light in unique ways. They are typically designed by hand based on the careful analysis of their bands and mode profiles, but recent theoretical advances have revealed new and powerful insights into the connection between band symmetry, connectivity, and topology. Here we propose a combined global and local optimization framework that integrates a flexible symmetry-constrained level-set parametrization … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 91 publications
(173 reference statements)
0
1
0
Order By: Relevance
“…We have demonstrated that this fractionalization comes from a counting mismatch of states and that the boundary-localized states associated with it are the consequence of the conservation of the number of degrees of freedom in the system, and do not require a fixed band filling (i.e., Fermi level). We have further demonstrated The framework presented here is readily generalizable to three-dimensional PhCs under crystalline symmetries [89,122]. Such three-dimensional PhCs, now a subject of active experimental exploration [123][124][125][126][127], exhibit several unique topological phases with associated bulk and boundary signatures.…”
Section: Discussionmentioning
confidence: 75%
“…We have demonstrated that this fractionalization comes from a counting mismatch of states and that the boundary-localized states associated with it are the consequence of the conservation of the number of degrees of freedom in the system, and do not require a fixed band filling (i.e., Fermi level). We have further demonstrated The framework presented here is readily generalizable to three-dimensional PhCs under crystalline symmetries [89,122]. Such three-dimensional PhCs, now a subject of active experimental exploration [123][124][125][126][127], exhibit several unique topological phases with associated bulk and boundary signatures.…”
Section: Discussionmentioning
confidence: 75%